AEO (Axiology, epistemology and ontology) workshop - Moris, Megawati (2020)
“Understanding on the concept of AEO (Axiology, Epistemology and Ontology). Applying the notion of AEO in Islamization of knowledge activities. At the end of this workshop all participants are expected to understand the concept of AEO and how they can be applied in their course. Each department is expected to cover AEO at least in an introductory core course.” (DDAAIL) The above defines our scope and limitation. **The lecture and workshop are preliminary steps to further discussion and before a proper, comprehensive and feasible course structure and content can be implemented.